2022
DOI: 10.1063/5.0087666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of barrier thickness on photoelectric properties of InGaN/GaN asymmetric multiple-quantum-well structure light-emitting diode

Abstract: GaN/GaInN asymmetric multiple quantum well light-emitting diodes with varying potential barrier thicknesses (5 and 15 nm) are grown by using metal organic chemical vapor deposition. The narrow barrier structure improves the performance of the device, including the super-linear increase of electroluminescence integral intensity, the mitigation of efficiency droop at high current density, the reduction of wavelength drift, the reduction of forward voltage, and the improvement of wall-plug efficiency. This is due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…These electric field values are consistent with Bernardini et al [59] and Chow et al [60,61]. It is also noted that the electric field is almost constant in the InxGa1-xN well, which leads to a linear form offset of conduction and valence bands in the wells [62]. In the GaN barrier, the linear electric field form leads to a parabolic offset form of conduction and valence bands [55], Figure 4.…”
Section: The 6-qwled Structuresupporting
confidence: 89%
“…These electric field values are consistent with Bernardini et al [59] and Chow et al [60,61]. It is also noted that the electric field is almost constant in the InxGa1-xN well, which leads to a linear form offset of conduction and valence bands in the wells [62]. In the GaN barrier, the linear electric field form leads to a parabolic offset form of conduction and valence bands [55], Figure 4.…”
Section: The 6-qwled Structuresupporting
confidence: 89%
“…As a result, the introduced holes typically concentrate in the quantum wells (QWs) closest to the p-GaN side, resulting in a smaller density of holes in other QWs and considerable electron losses, resulting in a reduction in overall efficiency. The asymmetric InGaN QW design has been found to be one of the most successful methods for improving carrier concentration in the active zone and minimizing electron loss from the wells [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the many QW regions with thin barriers, where hole transport and tunneling are better, more evenly distributed holes and a lower density of carriers can be obtained at a higher injected current density. Then, for all QWs, the hole can efficiently recombine with electrons, decreasing the excessive concentration of holes found in the first QW towards the p-type side and help in better radiative recombination [9].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, for stepped In 0.2 GaN 0.8 /GaN quantum well-LED structures, the researchers experimentally determined that the thin barrier structure enhanced the device's performance and decreased efficiency droop at high current density. This may be caused by poor hole tunneling through the thick barrier, causing electron leakage from the active region [8], while a theoretical study for parabolic In 0.2 GaN 0.8 /GaN quantum well-LED structures found that a thick barrier structure significantly increased efficiency [4].…”
Section: Introductionmentioning
confidence: 99%